Pitch angle diffusion by whistler mode waves in the jovian magnetosphere and diffuse auroral precipitation - Tripathi A.K.; Singhal R.P.; Singh K.P.; Singh O.N. (My University, 2025)
Bounce-averaged pitch angle diffusion rates of electrons due to whistler mode waves have been calculated in the Jupiter's magnetosphere. Variations of electron density, magnetic field, wave intensity and upper cut-off frequency along the particle bounce trajectory have been taken into account. Field line tracing is performed to obtain the loss-cone size associated with the VIP 4 magnetic field model including the external field due to azimuthal current sheet. Numerical calculations have been carried out at L shells 10, 12, 15, 18, and 20. The longitudinal variations of electron energy precipitation into the atmosphere leading to diffuse aurora have been modelled. It is found that observed wave amplitudes at L≤. 15 are insufficient to put electrons on strong pitch angle diffusion whereas at L=. 18 and 20 electrons of energies ≤30. keV can be put on strong diffusion. At L=. 10 electron energy precipitation supports auroral brightness of 25. kR in the northern and 36. kR in the southern hemisphere at west longitude ~10-60°. At shells L=. 12 and 15 auroral brightness less than 10. kR is obtained. This is in accord with Voyager observation of jovian UV aurora just beyond the Io torus (7-12. RJ). At L=. 18 maximum auroral brightness 73. kR in the northern hemisphere at west longitude of 163° and 30. kR in the southern hemisphere for west longitudes ≤50° are obtained. This is in agreement with the diffuse auroral brightness measured by Hubble Space Telescope (HST). Observations of longitudinal variation of diffuse auroral brightness are, however, required to ascertain the present findings. © 2013.